Understanding Consumers’ Intentions to Purchase Electric Motorcycles: Insights from the Theory of Planned Behavior - Tjokrosaputro, Miharni; Indrawan, Satriya Cahya (Jurnal Manajemen, 2025)
Global warming is a global issue, and electric vehicles provide an effective solution to help lower CO2 emissions. This study adopts and employs a descriptive quantitative approach to examine the factors influencing the purchase intention of electric motorcycles through the Theory of Planned Behavior (TPB) lens. Specifically, it investigates how perceived behavioral control and subjective norms affect purchase intention, with consumer attitudes mediating these effects. Using a purposive sample of 206 respondents, 202 of whom were valid participants currently using electric motorcycles, data were gathered through online surveys and analyzed with SmartPLS-SEM. Findings of this study resulted  that subjective  norms and perceived behavioral control significantly affect purchase intention, with attitude mediating between subjective norms and purchase intention. These insights offer valuable guidance for industry professionals, especially in promoting electric motorcycle adoption and fostering positive consumer attitudes.